2008
DOI: 10.1093/carcin/bgn212
|View full text |Cite
|
Sign up to set email alerts
|

Manganese superoxide dismutase (MnSOD) gene polymorphism, interactions with carotenoid levels and prostate cancer risk

Abstract: In this cohort of mainly white men, the MnSOD gene Ala16Val polymorphism was not associated with total or aggressive prostate cancer risk. However, men with the MnSOD Ala/Ala genotype who had low long-term lycopene status had a higher risk of aggressive prostate cancer compared with individuals with the other genotypes. These results are consistent with findings from earlier studies that reported when antioxidant status is low, the MnSOD Ala/Ala genotype may be associated with an increased risk of aggressive p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
63
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(71 citation statements)
references
References 35 publications
(41 reference statements)
7
63
0
1
Order By: Relevance
“…Furthermore, the MnSOD rs4880 polymorphism was not found to be associated with prostate cancer risk. [27,28] However, interestingly, Choi et al [27] reported that the risk of prostate cancer increased with iron intake among men homozygous for the TT genotype (P for trend = 0.02). Mikhak et al [28] also reported that the CC genotype plus a low lycopene level is associated with a higher risk of aggressive prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the MnSOD rs4880 polymorphism was not found to be associated with prostate cancer risk. [27,28] However, interestingly, Choi et al [27] reported that the risk of prostate cancer increased with iron intake among men homozygous for the TT genotype (P for trend = 0.02). Mikhak et al [28] also reported that the CC genotype plus a low lycopene level is associated with a higher risk of aggressive prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…[25,30] In mitochondria, higher MnSOD expression may result in elevated H 2 O 2 levels, which are produced by the dismutated superoxide anion, and these may induce toxicity if glutathione peroxidase activity or antioxidant levels are low [30]. However, when antioxidant levels are adequate, the increased rate of superoxide anion quenching afforded by the C genotype may be beneficial [28]. In this study, we observed that women with the C genotype and a higher antioxidant status appeared to be protected from cervical carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, of the 22 studies (Wang et al, 2001;Woodson et al, 2001;Lin et al, 2003;Liu et al, 2004;Wang et al, 2004;Li et al, 2005;Taufer et al, 2005;Ho et al, 2006;Choi et al, 2007;di Martino et al, 2007;Ergen et al, 2007;Kang et al, 2007;Arsova-Sarafinovska et al, 2008;Iguchi et al, 2008;Mikhak et al, 2008;Bica et al, 2009;Cheng et al, 2009;Iguchi et al, 2009;Sun et al, 2009;Zejnilovic etal., 2009), the sample size ranged between 100 and 3,030, and there were twelve studies on prostate cancer, four studies on esophageal cancer, and six studies on lung cancer. All studies, except for five of them (Taufer et al, 2005;Bica et al, 2009;Sun et al, 2009;Zejnilovic et al, 2009), indicated that the distribution of genotypes in the controls was consistent with HardyWeinberg equilibrium, while only one study conducted by Lin et al (2003) contained no data for Hardy-Weinberg equilibrium.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Li et al reported an impressive 10-fold swing in the risk of aggressive prostate cancer among men who expressed the AA genotype between the lowest quartile of total antioxidant consumption and the highest, with those consuming the lowest levels of dietary antioxidants being at the greatest risk (Li et al, 2005). Similarly, it was reported that there was a 3-fold increase risk of aggressive prostate cancer for AA men with low carotenoid status (P = 0.02, confidence interval: 1.37-7.02) (Mikhak et al, 2008). As originally proposed by Li et al, it is therefore possible that increased mitochondrial transport of MnSOD as a consequence of a codon 16 alanine is beneficial when antioxidant activity is high and the MnSOD dismutation product, H 2 O 2 , can be reduced to water (Li et al, 2005).…”
Section: Epidemiological Evidence For a Role Of Mnsod In Cancermentioning
confidence: 95%
“…It is difficult to arrive at a clear indication as to whether MnSOD levels are beneficial or harmful to patients with cancers because, as recently summarized, the levels of MnSOD in tumors can be higher or lower than that observed in the corresponding normal tissue (Dhar and St Clair, 2012). However, a variant MnSOD allele encoding an alanine (A) rather than a valine (V) at codon 16 has been described, and in several reports it has been associated with an elevated cancer risk, including the risk of prostate cancer, in human epidemiological studies (Li et al, 2005;Sutton et al, 2006;Kang et al, 2007;Mikhak et al, 2008). As a consequence of alanine being at this position in the mitochondrial import signal peptide, there is increased transport of MnSOD into the mitochondria as well as increased MnSOD mRNA stability (Sutton et al, 2005).…”
Section: Epidemiological Evidence For a Role Of Mnsod In Cancermentioning
confidence: 99%